Homogenitas Pilihan: Studi Kasus Kolonialisme dan Operasi Koteka 1970 - Aji Dwiatmaja, Ignatius (Eastasouth Institute, 2025)
This study examines the cultural and human rights implications of the forced displacement of traditional Papuan attire, *koteka*, through the Indonesian government's “Operasi Koteka” in 1970. Employing a qualitative case study approach and utilizing Georg Simmel’s concept of the